2015
DOI: 10.5194/amt-8-5289-2015
|View full text |Cite
|
Sign up to set email alerts
|

Gas adsorption and desorption effects on cylinders and their importance for long-term gas records

Abstract: Abstract.It is well known that gases adsorb on many surfaces, in particular metal surfaces. There are two main forms responsible for these effects (i) physisorption and (ii) chemisorption. Physisorption is associated with lower binding energies in the order of 1-10 kJ mol −1 , compared to chemisorption which ranges from 100 to 1000 kJ mol −1 . Furthermore, chemisorption only forms monolayers, contrasting physisorption that can form multilayer adsorption. The reverse process is called desorption and follows sim… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
28
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 27 publications
(30 citation statements)
references
References 16 publications
(13 reference statements)
1
28
1
Order By: Relevance
“…A significant difference between this study and the previous studies (Leuenberger et al, 2015;Brewer et al, 2018;Schibig et al, 2018) is the onset of adsorption effects. All previous studies have shown that for high pressure cylinders, usage below 20 bar is problematic.…”
Section: Discussioncontrasting
confidence: 79%
“…A significant difference between this study and the previous studies (Leuenberger et al, 2015;Brewer et al, 2018;Schibig et al, 2018) is the onset of adsorption effects. All previous studies have shown that for high pressure cylinders, usage below 20 bar is problematic.…”
Section: Discussioncontrasting
confidence: 79%
“…There has been much interest of late in the initial adsorption of carbon dioxide (CO 2 ) in air balance mixtures from the initial filling of a cylinder followed by desorption as the pressure in the cylinder is reduced, resulting in an increase in the mole fraction of CO 2 (Leuenberger et al, 2015;Miller et al, 2015). This adsorption/desorption can be modeled for different cylinder volumes using the Langmuir isotherm (Langmuir, 1916(Langmuir, , 1918.…”
Section: Stability As a Function Of Pressurementioning
confidence: 99%
“…as isotopic abundances in the troposphere are considered to be constant (Junk and Svec, 1958;Baertschi, 1976;Li et al, 1988;Barkan and Luz, 2005). Because differences between isotopic ratios of N 2 , O 2 , and Ar in the AIST reference air and air samples at Hateruma were small enough to be negligible, their fractionations due to preparation of the AIST reference air are ignored.…”
Section: Weighing Procedures For a Cylindermentioning
confidence: 99%
“…However, there are many deterioration risks of the O 2 /N 2 ratio in aluminium cylinders used for reference air and the primary standard mixtures. These include fractionations of O 2 and N 2 induced by pressure, temperature, and water vapour gradients (Keeling et al, 1998b); adsorption-desorption of the constituents on the inner surface (Leuenberger et al, 2015); and permeation or leakage of the constituents from or through the valve (Sturm et al, 2004;Keeling et al, 2007). In order to avoid these risks, the cylinders are handled in accordance with certain best practices, including orienting cylinders horizontally to minimize thermal and gravitational fractionation (Keeling et al, 2007;Leuenberger et al, 2015).…”
Section: Introductionmentioning
confidence: 99%